2014
DOI: 10.1007/s00484-014-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Semen variables and sperm membrane protein profile of Saanen bucks (Capra hircus) in dry and rainy seasons of the northeastern Brazil (3°S)

Abstract: The Saanen is a highly productive breed, and for this reason, it has been raised in Brazil, but mostly under climate conditions completely different from where the breed originated. The objective of this study was to investigate variations in semen parameters and sperm membrane proteins from Saanen bucks (n = 7) raised in Northeastern Brazil, during dry season (September, October, and November) and rainy season (March, April, and May). We showed that during the dry season, sperm motility, concentration, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…In this study, the semen collection of Senduro bucks seems to be more profitable when conducted during the rainy season compared to dry season as indicated by higher CONC, IMOT, and PTMOT. This current finding is in corresponds with other studies which also revealed that the bucks had higher sperm concentration and motility in the rainy season than dry season [6,7]. The higher sperm concentration in the dry season as compared to dry season also previously reported in other livestock such as cattle and buffalo [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the semen collection of Senduro bucks seems to be more profitable when conducted during the rainy season compared to dry season as indicated by higher CONC, IMOT, and PTMOT. This current finding is in corresponds with other studies which also revealed that the bucks had higher sperm concentration and motility in the rainy season than dry season [6,7]. The higher sperm concentration in the dry season as compared to dry season also previously reported in other livestock such as cattle and buffalo [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…Proteins extracted from oviduct and uterus tissue were separated by 2‐D SDS‐PAGE based on a protocol previously described (Van Tilburg et al, ), with modifications. For focalization (first dimension), the samples were solubilized in rehydration solution (7 M Urea, 2 M Thiourea, 2%CHAPS, 1% DTT, 2% buffer IPG pH 4 −7% and 0.002% bromophenol blue (GE Healthcare®, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Spots identified in the uterine tissue and oviduct maps and differentially expressed according to treatments were excised from gels and digested as described by van Tilburg et al (). Tryptic peptides were separated in BEH300 C18 columns (100 μm × 100 mm) using the nanoAcquity™ (Waters, USA) system and eluted at 600 μl/min with acetonitrile gradient (5%–85%) containing 0.1% formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The specific synthesis of actin family proteins in the testes occurs at the end of spermatid differentiation. They were studied in bovine (Byrne et al, 2012) and ovine (van Tilburg et al, 2013) spermatozoa.…”
Section: Discussionmentioning
confidence: 99%